Discovery of entomopathogenic fungi across geographical regions in southern China on pine sawyer beetle Monochamus alternatus and implication for multi-pathogen vectoring potential of this beetle - Wu, Shengxin; Wu, Jia; Wang, Yun; Qu, Yifei; He, Yao; Wang, Jingyan; Cheng, Jianhui; Zhang, Liqin; Cheng, Chihang (Frontiers in Plant Science, 2022)
Entomopathogen-based biocontrol is a crucial strategy to block transmission of vector-borne diseases; however, few cross-latitudinal investigations of entomopathogens have been reported for populations of vector pests transmitting woody plant diseases in forest ecosystems. The pine sawyer beetle Monochamus alternatus is an important wood borer while also a major vector transmitting the pine wilt disease, facilitating invasion success of pinewood nematode Bursaphelenchus xylophilus in China. Due to limited geographical breadth of sampling regions, species diversity of fungal associates (especially entomopathogenic fungi) on M. alternatus adults and their potential ecological functions have been seriously underestimated before. Here, through traditional fungal isolation with morphological and molecular identification, a total of 640 fungal strains (affiliated to 15 genera 39 species) were isolated from 81 beetle cadavers covered by mycelia or those symptomatically alive across 5 regional populations of this pest in southern China. Multivariate analyses revealed significant difference in the fungal community composition among geographical populations of M. alternatus, presenting region-specific characteristics, while no significance was found in fungal composition between beetle genders or among body positions. Four region-specific fungi including Lecanicillium attenuatum (in Zhejiang Province), Aspergillus austwickii (in Sichuan Province), Scopulariopsis alboflavescens (in Fujian Province) and A. ruber (in Guangxi Province) as well as another 3 fungal species Beauveria bassiana, Penicillium citrinum and Trichoderma dorotheae showed significantly stronger entomopathogenic activities than others. Additionally, insect-parasitic entomopathogenic fungi (A. austwickii, B. bassiana, L. attenuatum and S. alboflavescens) exhibited less to no obviously phytopathogenic activities to the host pine Pinus massoniana, while P. citrinum, Purpureocillium lilacinum and certain species of Fusarium spp., isolated from M. alternatus body surfaces, were remarkably higher in phytopathogenicity. Our results provided a broader view of entomopathogenic fungal community on the vector beetle M. alternatus, some of which were even reported for the first time on Monochamus spp. in China. Moreover, this beetle might be more highly-risk and complicated than previously thought in pine forests, as a potential multi-pathogen vector of both phytopathogenic nematode and fungi.